Water quality monitoring following Hurricanes Katrina and Rita. (28th February 2008) - Roper, William E.; Weiss, Kevin J.; Wheeler, James F.
Following the passage of Hurricane Katrina, New Orleans was left with 80% of its land area flooded. In some locations, the flood waters were over 30 feet deep. In the heat and stagnation, the waters quickly became heavily polluted. Pump out operations began in early September 2005 to get the city dried out quickly. Lake Pontchartrain was the primary receiving water body. A variety of approaches were evaluated to achieve treatment with minimal impact on pumping operations. Some of these included; sorbet booms in the channels and the lake near outfalls, oil and debris removal skimmers in channels and near outfalls, sediment control devises for hot spots, application of flocculation chemicals, aerators in the channels and near the outfalls, etc. Over 100 water quality sampling sites were set-up throughout the city to characterise water conditions as the pump out proceeded. High risk areas were identified in a dynamic process and decisions make for best corrective action. Lake Pontchartrain continues to be monitored and long term rehabilitation efforts will be predicated on water quality monitoring results. Lessons learned from a water quality perspective during this massive disaster are presented with the goal of assisting future recovery efforts.